Demokrasi dan Sistem Pemerintahan - Noviati, Cora Elly (Jurnal Konstitusi, 2013)
Democracy provides an understanding that the source of power is the  people with an understanding that people will give birth to a rule that will benefit and protect their rights. In order for that to happen, a rule is needed to support the   idea and serves as the foundation in the life of the state to guarantee and protect the rights of the people. Such rule is called The Constitution.The understanding on the highest power itself does not need to be understood in the sense of absolute monistic and unlimited, because it is in itself that the supreme power which is in the hands of the people is limited by the agreement they set forth together as outlined in the formulation of  the  constitution  they  made and promulgated especially on the founding of the state. This  is  what  is called the  social  contract  between  citizens  as  reflected  in  the  constitution.  It  is that constitution which limits and regulates how the sovereignty of  the  people is channeled, executed and maintained in  state  activities  and  day-to-  day running of the government. In essence, within the idea of popular sovereignty,  it remains to be guaranteed that the people are the true owners of the State with  all its authority to  carry  out  all  the  functions  of  state  power,  both  in  the  field of legislative, executive, and  judiciary.  It  is  the  people  who  have  the  authority  to plan, organize, implement, and  conduct  monitoring  and  assessment  of  the implementation of the power functions. Even further, it is for the benefit of the people that every activities aimed at. It is for the people that all the benefits gained from the functioning and the organization of the state are intended. This is the idea of popular sovereignty or democracy that is totally of the people, for the people, by the people, and with  people.